Vertical jump development in elite adolescent volleyball players: Effects of sex and age - Polakovicová, M.; Vavák, M.; Ollé, R.; Lehnert, M.; Sigmund, M. (Acta Gymnica, 2018)
Background: Vertical jump is one of the most prevalent activities performed in volleyball. During adolescence, boys and girls undergo substantial changes in physiological and anthropometric characteristics that influence vertical jump performance.